Diagnostic accuracy of instantaneous wave-free ratio at rest and during dobutamine provocation to assess myocardial bridging relevance. (3rd October 2022) - Aleksandric, S; Al-Lamee, R; Djordjevic-Dikic, A; Giga, V; Tesic, M; Banovic, M; Zobenica, V; Vukcevic, V; Tomasevic, M; Stojkovic, S; Orlic, D; Nedeljkovic, M; et al.
Abstract: Background: Diastolic fractional flow reserve (d-FFR) during dobutamine provocation (DOB) was found to be a more reliable physiological index for the functional assessment of myocardial bridging (MB). However, d-FFR calculation is complicated and time-consuming, and therefore several authors have suggested the use of instantaneous wave-free ratio (iFR) to overcome these issues. Purpose: The aim of our study was to assess diagnostic performance of d-FFR and iFR at rest and during DOB with exercise-induced myocardial ischemia as reference. Methods: Twenty-four symptomatic patients (17 males, mean age 58±8 years) with MB and systolic compression ≥50% diameter stenosis on the left anterior descending (LAD) artery were included. Exercise stress-echocardiography test (SE), and both d-FFR and iFR in the distal segment of LAD at rest and peak DOB (30–50μg/kg/min), were performed in all patients. Optimal cut-off values and diagnostic performance of resting and hyperemic d-FFR and iFR were assessed using SE. Results: Exercise-SE was positive for myocardial ischemia in 7/24 patients (29%). The area-under-the-receiver-operating-characteristic curve (ROC-AUC) for exercise-induced myocardial ischemia was 0.64 (95% CI: 0.400–0.885) for resting d-FFR, 0.62 (95% CI: 0.378–0.866) for resting iFR, 1.000 (95% CI: 0.999–1.000) for d-FFR at peak DOB, and 0.96 (95% CI: 0.895–1.000) for iFR at peak DOB. No significant difference in ROC-AUC was observed between d-FFR and iFR at peak DOB (p=0.243). The best cut-off value for both d-FFR and iFR at peak DOB was <0.76 with similar sensitivity and negative predictive values (100 vs. 100% for both), but lower specificity and positive predictive value for iFR in identifying MB associated with exercise-induced ischemia (94% vs. 82%; 88% vs. 70%, respectively). Compared with exercise-induced myocardial ischemia, the diagnostic accuracy of d-FFR and iFR at peak DOB was 96% (kappa=0.903, p<0.001) and 88% (kappa=0.731, p<0.001), respectively. Conclusions: iFR during DOB provocation showed similar diagnostic accuracy as d-FFR to identify the functionally significant MB when compared with exercise-induced myocardial ischemia. Funding Acknowledgement: Type of funding sources: None.